Increasing the mobility of cabins of dynamic simulators of mobile machines - Яглинский, Виктор Петрович; Обайди, Аймен Сабах; Фелько, Николай Вячеславович (Technology audit and production reserves, 2014)
Driving combat mobile machines (MM) is very difficult and dangerous operation, which requires making quick decisions on roadholding and instant reactions on the movement change by manipulating driving devices. Therefore, the problem of increasing the MM crew training quality is very important, and improving the complex of imitating motions of the simulator cabin, bringing them closer to the real conditions of operation and behavior in extreme situations is an urgent issue. Known simulator systems for MM crews either do not create acceleration load, or have limited spatial working area. Using the proposed simulator design, based on the hexapod with mobile two-coordinate basis has allowed to increase the dimensions of spatial working area and the mobility degree, improve maneuverability and ability to implement complex imitating motions of the crew cabin (MM). As a result of the studies, mathematical control models of kinematics parameters of the simulator, imitating the MM movement on water in conditions of pitching and rolling, or by land with the challenging terrain are developed. Levels of the acceleration effect on the MM crew when practicing maneuvers, such as sidewise one-way or two-way skiddings, corresponding to the real operating conditions are determined. The main value of the research results lies in creating control tools and means of motion parameters of cabin of the proposed simulator design, enhancing its mobility and subsequent effectiveness of MM crew training for real extreme conditions.